Determination of Physical and Mechanical Properties of Waste Paper Boards Supported by Wood Chips and Chopped E-glass Fiber - Sözen, Eser; Sözen, Eser (Zagreb Univ, Fac Forestry, 2022)
Today, legal regulations, along with social awareness, have made waste management a necessity. Depending on the type of waste, technological developments have enabled an increase in the number of approach-es, e.g., reusing, recycling, and manufacturing of different products. In this study, low-density boards were pro-duced using different proportions of office waste paper, wood chips, and chopped E-glass fiber. Waste paper and glass fiber formed the middle layer of the boards and wood chips comprised the surface layers. The density, water absorption, and thickness swelling properties of the boards were investigated. Among the mechanical properties, the modulus of rupture, modulus of elasticity, and internal bond strength were determined. The use of wastepaper led to a reduction in the modulus of rupture and modulus of elasticity of the boards. An increase in the glass fiber ratio contributed positively to the water absorption and thickness swelling properties, whereas it directly led to decreases in the internal bond strength, and the modulus of rupture and modulus of elasticity values. Nonetheless, the low-density boards were able to meet the minimum modulus of rupture and modulus of elasticity specified in ANSI 208.1 standards, while only one variation met the IB requirements.
Keywords: Office Waste Paper; Paper Board; Wood Chips; Chopped Glass Fiber